Keselarasan Faktor Lingkungan, Kapabilitas Manufaktur, Orientasi Kewirausahaan dan Kinerja Perusahaan - Thabrani, Gesit; Susanto, Perengki; Masdupi, Erni (Jurnal Ecogen, 2025)
Small and medium enterprises (SMEs) have proven to have a strategic role in supporting the Indonesian economy. However, the performance of SMEs has not shown excellence in dealing with uncertain environmental conditions. This study looks at the alignment between environmental factors, manufacturing capabilities, entrepreneurial orientation and Company performance using a quality function deployment (QFD) approach. The results of the study show that to deal with environmental factors, SMEs need to focus on quality, innovatively oriented, which has an impact on marketing performance.Keywords:    kinerja perusahan, faktor lingkungan, kapabilitas manufaktur, orientasi kewirausahaan, house of quality